A New Extension of the ELECTRE Method Based Upon Interval Type-2 Fuzzy Sets for Green Logistic Service Providers Evaluation - Celik, Erkan; Gumus, Alev Taskin; Erdogan, Melike (AMER SOC TESTING MATERIALS, 2016)
Increase in environmental pollution makes companies give more importance to this issue, and as such, there is a need to take into account the necessary precautions. In particular, logistics service providers who are interwoven with the environment should apply some policies to increase environmental awareness. In this paper, we extended the ELECTRE method and proposed a new methodology for handling fuzzy multi criteria decision making problems based upon interval type-2 fuzzy sets. Interval type-2 fuzzy sets provided more df to reflect the uncertainty and the fuzziness of the real applications. An empirical study was presented in order to evaluate the green logistics service providers. A sensitivity analysis was applied to discuss and evaluate the greenness of the logistic service providers.
Keywords: green logistic service providers; multi criteria decision making; interval type-2 fuzzy sets; ELECTRE; GROUP DECISION-MAKING; SUPPLY CHAIN MANAGEMENT; ENVIRONMENTAL CRITERIA; MCDM METHOD; SELECTION; TOPSIS; MODEL; QUALITY; PERFORMANCE; INFERENCE; Materials Science